Determinação e distribuição de cobre, ferro e zinco em Physalis angulata por espectrometria de emissão óptica com plasma acoplado indutivamente - PEREIRA, Cecília Correia (2023)
The Amazon has a variety of fruits that are a nutricional source of great importante for the human body capable of reducing the incidence of various diseases. Therefore, the presente study aimed to determine the total levels of copper, iron and zinc in the pulp of physalis angulata (camapu). First, lipid extraction was carried out in camapu using 30 ml of a mixture of chloroform and metanol (2:1). The protein fractions were obtained after sequential removal using 20 ml of four diferente extracting solution (water, sodium chloride 0,5 mol/ L, acetic acid 50% v/v and sodium hydroxide 0,05 mol/L). A sample of camapu and the protein fractions were digested in a microwave heat oven using 50% nitric acid, hydrogen peroxide and water. The solution of the propodes procedure was evaluated using the addition nd recovery method in digests and protein extracts. The total contentes of Cu, Fe and Zn in the camapu digestion were 10,8; 32,7 and 22,0, mg kg-1, respectively. In the protein fractions, levels of all trained analytes were found. In the lipid fraction. Cu levels were obtained (0,2 mg kg-1); Fe (0,5 mg kg-1) and Zn (0,07 mg kg-1). High levels of Cu (3,4 mg kg-1) e Zn(14,9 mg kg-1) were found associated with albumin ( water extration) when compared to other extractants. On the other hand, high iron levels ( 8,8 mg kg-1) were obtained in the fraction refering to globulins ( extraction wuth NaCl). The one presented had a higher iron contente (10,7 mg kg-1). The data were subjected to analysis of variance and mean comparison test using the Tukey test (p < 0,05 ). Totl protein concentration was determined by the Bradford method. It was found that the amount of albumins ( 5,74 mg kg- 1)extrated was greater when compared to globulin ( 0,28 mg kg-1), glutelin 1 (4,46 mg kg-1) and glutelin 2 (0,46 mg kg-1). The proposed sequential extration procedure was suitable for determining Cu, Fe and Zn associated with scientific metalloproteins. Additional studies on bioavailability are necessary to verify the amount of these nutrientes that can be absorbed by the bory.